Legal Responsibility Of Hospital For Refusal To Provide To Provide Emergency Medical Services In Case Of Meternal And Neonatal Death In Papua Province - Jeuquline Octoviana Tentua; Ahmad Ma’mun Fikri (UNIVERSITAS PAKUAN, 2026)
This study is motivated by the case of Irene Sokoy, a pregnant woman, and her unborn child, who died after allegedly being refused medical services by four hospitals in Papua Province. This incident constitutes a legal event that reflects a serious failure in the healthcare service system. This study aims to analyze the construction of hospital legal liability in cases involving the sequential refusal of emergency patients and to examine how the law can play a more active role in addressing refusals of medical services that may endanger patients’ lives. It also seeks to identify the forms of legal responsibility that may be imposed on hospitals when the refusal of emergency services results in harm to patients. This research uses a normative juridical method with statutory, conceptual, and comparative law approaches. The findings indicate that the refusal of services by four hospitals cannot be viewed as isolated violations, but rather as a series of cumulative unlawful acts. This study emphasizes the need to strengthen the principle of a zero-refusal policy and to reform the national referral system. Furthermore, the findings show that the refusal of emergency medical services by hospitals constitutes a violation of their legal obligations as stipulated in Law Number 44 of 2009 on Hospitals and Law Number 17 of 2023 on Health. Hospitals may be held legally accountable in the form of civil, criminal, and administrative liability if they are proven to have refused services resulting in patient death. Keywords: Legal Liability, Hospitals, Emergency Services, Sequential Refusal, Papua. This study is motivated by the case of Irene Sokoy, a pregnant woman, and her unborn child, who died after allegedly being refused medical services by four hospitals in Papua Province. This incident constitutes a legal event that reflects a serious failure in the healthcare service system. This study aims to analyze the construction of hospital legal liability in cases involving the sequential refusal of emergency patients and to examine how the law can play a more active role in addressing refusals of medical services that may endanger patients’ lives. It also seeks to identify the forms of legal responsibility that may be imposed on hospitals when the refusal of emergency services results in harm to patients. This research uses a normative juridical method with statutory, conceptual, and comparative law approaches. The findings indicate that the refusal of services by four hospitals cannot be viewed as isolated violations, but rather as a series of cumulative unlawful acts. This study emphasizes the need to strengthen the principle of a zero-refusal policy and to reform the national referral system. Furthermore, the findings show that the refusal of emergency medical services by hospitals constitutes a violation of their legal obligations as stipulated in Law Number 44 of 2009 on Hospitals and Law Number 17 of 2023 on Health. Hospitals may be held legally accountable in the form of civil, criminal, and administrative liability if they are proven to have refused services resulting in patient death. Keywords: Legal Liability, Hospitals, Emergency Services, Sequential Refusal, Papua.